Null mutants of Saccharomyces cerevisiae Cu,Zn superoxide dismutase: characterization and spontaneous mutation rates. - Gralla, E B (1991)
Deletion-replacement mutations of the Saccharomyces cerevisiae Cu,Zn superoxide dismutase gene were constructed. They were exquisitely sensitive to redox cycling drugs and showed slight sensitivity to other agents. The aerobic spontaneous mutation rate was three- to fourfold higher in sod1 delta 1 mutants, while the anaerobic rate was similar to that of the wild type.